Analysis on the work safety level in different provinces and regions of China. Issue 1 (10th December 2019) - Wu, Daming
Abstract: The work safety level is a reflection of the work safety situation, but in the past, we simply used a single absolute indicator or a single relative indicator to measure the work safety level, which is inadequate. This paper chooses five relative indicators and uses grey fixed weight clustering method to give a comprehensive evaluation of the work safety level in different provinces. According to the evaluation results, we grade the work safety level of geographic and economic regions, and find the gap in different provinces and regions. Our analysis suggests that the work safety level in different provinces and regions basically accords with the stage of industrialization process, but the fluctuated data analysis indicates that the theory of the relationship between the work safety and industrialization process has its defects, and the warped‐tail phenomenon of work safety level in the final and mature stage of industrialization process is thus pointed out. Taking the comparison between Henan and Shanghai as an example of the analysis of the warped‐tail phenomenon, the factors related to the work safety level in the final and mature stage of industrialization process are discussed.